Hadith #3758 - Sunan Abi Dawud - Abdullah bin 'Ubaid bin 'Umayr عبد الله بن عبيد بن عمير; Abu Bakr al-Hanfi عبد الكبير بن عبد المجيد- أبو بكر الحنفي; al-Dahhak bin 'Uthman bin 'Abdullah الضحاك بن عثمان بن عبد الله بن خالد; Ali bin Muslim bin Sa'id علي بن مسلم بن سعيد الطوسي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Prayer should not be postponed for taking meals nor for any other thing.
Grade: Da'if